2014
DOI: 10.2106/jbjs.m.00299
|View full text |Cite
|
Sign up to set email alerts
|

ACL Reconstruction: Do Outcomes Differ by Sex?

Abstract: Results of ACL reconstruction were similar in male and female patients. More high-quality studies are needed to further evaluate these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
57
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(67 citation statements)
references
References 33 publications
(92 reference statements)
6
57
2
2
Order By: Relevance
“…47 In the same study, the percentage of patients with a pivot shift test grade other than 0 was 12% in males and 20% in females. However, the meta-analysis indicated that this difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…47 In the same study, the percentage of patients with a pivot shift test grade other than 0 was 12% in males and 20% in females. However, the meta-analysis indicated that this difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 81%
“…However, the meta-analysis indicated that this difference was not statistically significant. 47 Other studies have reported significantly greater side-to-side differences in AP knee laxity in females than males for both the patellar tendon (up to 1 mm) 13 and hamstring tendon (up to 1.6 mm) 4, 8, 13, 18, 35, 43 grafts after ACL reconstruction. These findings compare with our findings of significantly greater side-to-side differences in AP knee laxity in female pigs than males by 1.4 mm (at 30° of knee flexion).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations